Young Muslims’ Financial Behavior: Money Attitudes and Financial Literacy by Debt Status - Nuwailah; Effendi, Jaenal; Ermawati, Wita Juwita (Review on Islamic Accounting, 2024)
The increasing trend in household consumption debt in Indonesia, especially through digital lending platforms, has become a societal concern. From an Islamic perspective, debt is governed by ethical principles that emphasize fulfilling obligations responsibly and prudently. Achieving this requires self-discipline, supported by informed financial attitudes and knowledge. This study analyzes the effects of attitudes toward money and financial literacy, specifically debt and Islamic financial literacy, on the financial management behavior of young Muslim adults in Indonesia. It also examines differences in these effects between individuals with debt and those without. Data from 245 respondents were collected using structured questionnaires, analyzed through multiple linear regression, and further tested using the Chow Test to compare the two groups. Results indicate that attitudes toward money, debt, and Islamic financial literacy positively affect financial management behavior. However, in partial analysis, only Islamic financial literacy does not significantly impact financial management behavior. Additionally, comparisons between the two groups revealed no significant differences in financial management behavior between those with debt and those without, likely due to similar financial management tendencies across both groups.